Технология сравнения эффективности методов оценивания и выбора альтернатив - Лисецкий, Ю.М. (Управляющие системы и машины, 2017)
Для сравнения эффективности различных методов оценивания и выбора альтернативных вариантов разработана технология определения наилучшего из группы методов по критерию минимума среднего количества изменений упорядочения альтернатив. Предложен алгоритм ее реализации. Для порівняння ефективності різних методів оцінювання та вибору альтернативних варіантів розроблено технологію визначення найкращого з групи методів за критерієм мінімуму середньої кількості змін упорядкування альтернатив. Запропоновано алгоритм її реалізації. To compare efficiency of different methods to estimate and choose among alternatives, there is proposed the technology the essence of which is finding the best method from the group based on criterion of the minimal average amount of variations to the ranking. The source data for the technology are alternative variants of the systems presented as the matrix of the alternative characteristic. There is executed proportional normalization of characteristics. Then different methods of estimation and selection produce different rankings of alternatives. There is proposed to use the ratio of the number of nonidentical rankings of alternatives to the amount of rankings as the indicator reflecting distortion of estimations. The comparison in pairs results in the matrix of the distortion of the results of the alternatives rankings by different methods. The matrix is used to calculate the average distortion of the results among the methods. The method with the lowest average amount of variations to the alternatives ranking is deemed effective. The offered technology offered can be algorithmized. The algorithm has been programmed in C++.